1093 Pyoderma Gangrenosum Complicating Surgery for Breast Cancer in A Patient with Insulin Treated Diabetes. A Case Report. (12th October 2021) - Croitoru, C; McGoldrick, C; Irwin, G
Abstract: Aim: Although rare, Pyoderma Gangrenosum (PG) occurs as a significant complication of breast surgery. The early manifestations are similar to necrotising wound infection, so diagnosis and correct management are often delayed. Method: We present the case of a 51-year-old female, diagnosed with multifocal right breast cancer, who underwent right sentinel lymph node biopsy and bilateral skin-spearing, nipple-sacrificing mastectomies with immediate implant reconstruction (patient's choice). Her medical history included type 2 diabetes on insulin, hypertension, and obesity. One week postoperatively the right breast wound showed signs of not healing. After 5 weeks of conservative management including input from tissue viability, wound debridement and negative pressure wound therapy (NPWT), the phenomenon of pathergy raised the clinical suspicion of PG which was confirmed histologically. Results: A multidisciplinary approach was instituted. The patient was started on steroid and non-steroid immune modulation therapy. She underwent further wound debridement, implant removal with NPWT and she received Tamoxifen as adjuvant chemotherapy had to be delayed. The wound healed 27 weeks after initial surgery. Conclusions: Pyoderma Gangrenosum is an ulcerative skin disorder of unknown aetiology which is associated with systemic illnesses. It needs to be recognised and requires aggressive systemic therapy. There is little information about its long-term evolution.